Preliminary Assessment of Building Damage Potential Due to Landslide (Case Study Gua Maria Kerep Ambarawa, Central Java) - Daniel Hartono; Maria Wahyuni; Budi Setiadi; Hermawan; Yohanes Yuli Mulyanto; Bryan Brama Ramadhana; Gatot Yuliyanto; Stelina Candita Gunawan Sin Sin Tan; Stefanie Virlanta Putri; Cahyo Priyo Sembodo (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Landslides are complex phenomena that are frequently interpreted differently across disciplines due to their mechanisms and impacts on both nature and society. This paper presents an assessment of landslide vulnerability in the Gua Maria Kerep Ambarawa (GMKA) area, a Catholic pilgrimage site in Central Java, Indonesia. The study highlights the need to identify and classify disaster-prone areas to facilitate effective regulation, site development, and disaster mitigation efforts. Focusing on GMKA, the research employs a phased vulnerability assessment approach to map potential sources of landslide hazards, particularly following a surface landslide during the early 2024 rainy season. The observations indicate that water seepage and soil saturation around the graveyard area were key contributing factors. The movement of soil under the surface was detected using georadar, which measures the shear wave velocity of the soil layer under the surface. Visual indicators, such as gaps in masonry, can serve as an effective hazard prevention measure prior to conducting instrumental inspections.